The Food Security Simulator Ethiopia (FSSE): An innovative household food security assessment tool - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
First presentation of the Food Security Simulator Ethiopia (FSSE) at the Hybrid Research & Policy Conference for Livestock, Gender, and Agency Amid Conflict in Ethiopia, December 11th, 2024.